Preparation method and application of MXene / aramid nanofiber electromagnetic shielding hydrogel

Through the combination of MXene and aramid nanofiber hydrogel, the problem of MXene material being easily oxidized and less conductive in the air is solved, forming an efficient electromagnetic shielding and sensing material, achieving an electromagnetic shielding efficiency of 35.7dB and 110% Resistance change rate, suitable for electromagnetic shielding and human motion sensing.

CN119306973APending Publication Date: 2025-01-14SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411315131.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

MXene materials are prone to oxidation in the air and are sensitive to moisture, resulting in insufficient stability and sustainability in actual applications. They also reduce electrical and thermal conductivity after being combined with fiber-based materials, affecting electromagnetic shielding performance.

Method used

The preparation method of MXene/aramid nanofiber electromagnetic shielded hydrogel is adopted. By mixing Ti3C2Tx MXene with liquid metal ultrasonic, adding deprotonated aramid nanofibers and PVA solution, then demolded after freezing, and preparing hydrogel to form a layer-like layer The structure is used to enhance electrical conductivity and mechanical properties, and improve electromagnetic shielding performance through tight bonding of hydrogen bonds.

Benefits of technology

It realizes efficient electromagnetic shielding performance and strain sensing performance. The electromagnetic shielding efficiency reaches 35.7dB and the unit thickness shielding efficiency is 37.5dB/mm. It has the characteristics of lightweight and shows a resistance change rate of 110% in human motion sensing. , meets the needs of electrical signal reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306973A_ABST
    Figure CN119306973A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an MXene / aramid nanofiber electromagnetic shielding hydrogel. The preparation method comprises the following steps: preparing an MXene / aramid nanofiber electromagnetic shielding hydrogel; the preparation method comprises the following steps: step 1, ultrasonically mixing a Ti < 3 > C < 2 > T < x > MXene dispersion liquid with liquid metal to obtain an MXene-coated LM mixed solution; step 2, adding an aramid nanofiber dispersion liquid prepared by deprotonation and a PVA (Polyvinyl Alcohol) solution into the MXene-coated LM mixed solution, and stirring to obtain a uniform solution; and 3, pouring the uniform solution into a mold, freezing, unfreezing, and demolding to obtain PVA-ANF / MXene-coated LM hydrogel, namely the MXene / aramid nanofiber electromagnetic shielding hydrogel. After the base material is prepared into the hydrogel, internal multiple reflection is structurally enhanced, and secondary pollution caused by reflection of electromagnetic waves is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogels, and in particular relates to a preparation method and application of a MXene / aramid nanofiber electromagnetic shielding hydrogel. Background Art

[0002] With the rapid development and widespread application of electronic devices, the problem of electromagnetic interference has become increasingly prominent. Electromagnetic radiation interference not only affects the normal operation of equipment, but also poses risks to information security and human health. Therefore, the development of efficient electromagnetic shielding materials is crucial to mitigate or control adverse electromagnetic radiation. In the field of electromagnetic shielding materials, MXene (two-dimensional transition metal carbide) has attracted much attention due to its excellent conductivity and mechanical properties. Compared with traditional metal materials, MXene has the characteristics of low density and adjustable structure, making it an ideal candidate for electromagnetic shielding materials. However, MXene materials face challenges such as easy oxidation in air and sensitivity to moisture, which limits their stability and sustainability in practical applications. Summary of the invention

[0003] In order to overcome the above problems existing in the prior art, the purpose of the present invention is to provide a method for preparing and applying a MXene / aramid nanofiber electromagnetic shielding hydrogel, so as to solve the problems of high brittleness of MXene materials and decreased electrical and thermal conductivity after being combined with fiber-based materials; after the matrix material is prepared as a hydrogel, the internal multiple reflections are structurally enhanced, thereby reducing secondary pollution caused by the reflection of electromagnetic waves.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is:

[0005] A method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel comprises the following steps;

[0006] Step 1: Ti3C2T x The MXene dispersion is ultrasonically mixed with the liquid metal to obtain a MXene@LM mixed solution;

[0007] Step 2: adding the aramid nanofiber dispersion prepared by deprotonation and the PVA solution to the MXene@LM mixed solution, and stirring to obtain a uniform solution;

[0008] Step 3: Pour the uniform solution into a mold and freeze it, then thaw and demold it to obtain PVA-ANF / MXene@LM hydrogel, i.e., MXene / aramid nanofiber electromagnetic shielding hydrogel.

[0009] Furthermore, in step 1, Ti3C2T x The preparation process of MXene is as follows:

[0010] Ti3AlC2 was etched with hydrofluoric acid (the molar ratio was 1:1) to obtain the Ti3C2T x MXene dispersion.

[0011] Furthermore, in step 1, the ultrasonic mixing process of MXene and liquid metal is as follows:

[0012] The MXene dispersion and liquid metal are mixed in a mass ratio (3:1-10:1), and after ultrasonication in an ultrasonic crusher, a MXene@LM mixed solution is formed.

[0013] The liquid metal is Ga.

[0014] Furthermore, in step 2, the preparation process of the aramid nanofiber dispersion is as follows:

[0015] KOH was dissolved in 1L of dimethyl sulfoxide, and then para-aramid fiber was added. After stirring, the mixture was centrifuged for 30 minutes at a centrifugal speed of 3000 rpm. Deionized water was added to obtain an aramid nanofiber dispersion, in which the mass ratio of KOH to para-aramid fiber was 3:2.

[0016] Furthermore, in step 2, the preparation process of the PVA solution is as follows:

[0017] Deionized water was added to 5 g of polyvinyl alcohol and heated to prepare a PVA solution with a mass fraction of 10%.

[0018] Furthermore, in the step 2, the MXene@LM mixed solution and the aramid nanofiber dispersion are mixed in a mass ratio of (2:8-8:2), and then 10% of the PVA solution is added and stirred (wherein the mixed dispersion and the PVA solution are mixed in a mass ratio of 1:1), and after the solution is uniform, a PVA-ANF / MXene@LM solution, i.e., a uniform solution, is obtained.

[0019] Furthermore, in step 3, the uniform solution is poured into a mold, frozen at a temperature of -1°C to 8°C, and then thawed and demolded to obtain the PVA-ANF / MXene@LM hydrogel.

[0020] The present invention also provides a MXene / aramid nanofiber electromagnetic shielding hydrogel, which has a layered structure inside. The structure is a compact structure. PVA, ANF and MXene@LM are closely connected through hydrogen bonds. The structure promotes the overlapping of the conductive matrix. MXene is beneficial to the formation of a conductive path by covering the Ga surface. There are also dense fibers between the layers. The aramid fibers and MXene are closely combined through hydrogen bonds. The hydrogel maintains high mechanical properties.

[0021] It provides the hydrogel with excellent mechanical and conductive properties. In addition, the unique network structure of the hydrogel further enhances the electromagnetic shielding effectiveness.

[0022] The present invention also provides an application of the MXene / aramid nanofiber electromagnetic shielding hydrogel, which is applied to the field of electromagnetic shielding, including electromagnetic shielding and strain sensing.

[0023] The electromagnetic shielding effectiveness can reach 35.7dB, and the thickness of the MXene / aramid nanofiber electromagnetic shielding hydrogel is 0.95-1.10mm.

[0024] Beneficial effects of the present invention:

[0025] The present invention provides a method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel having electromagnetic shielding performance and strain sensing performance, wherein Ti3C2T x The MXene dispersion and liquid metal are mixed and ultrasonically treated, and the MXene covers the Ga surface through electrostatic force and hydrogen bonding, thereby constructing a more continuous conductive path than a single MXene conductive path. Aramid nanofiber dispersion and PVA solution are added to the MXene@LM mixed solution, and the solution is poured into a mold after stirring, and the PVA-ANF / MXene@LM hydrogel is demolded after being frozen.

[0026] Compared with the electromagnetic shielding hydrogels that have been reported, it can not only shield 99.9% of electromagnetic waves, but also has the ability to sense human motion.

[0027] Specifically, MXene and liquid metal are ultrasonically mixed to construct a more continuous conductive path, which provides favorable conditions for the reflection loss of electromagnetic waves; the addition of aramid nanofibers improves the mechanical properties of the hydrogel matrix structure, and in addition, aramid nanofibers and MXene / LM form a layered structure. This layered structure is relatively compact and is formed by stacking aramid nanofibers and MXene / LM. The structure can make electromagnetic waves reflect multiple times inside; secondly, polyvinyl alcohol is introduced as a hydrogel crosslinker, and the network structure is compounded with the layered structure to form the overall structure of the hydrogel; finally, the prepared electromagnetic shielding hydrogel has a total shielding effectiveness of 35.7dB, and its shielding effectiveness per unit thickness is 37.5dB mm -1 , meeting the requirements of lightweight; the electromagnetic shielding hydrogel also has certain sensing properties. When it reaches 100% elongation, the resistance change rate is as high as 110%, and its electrical signals can also reflect the movement of different parts of the human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1This is a scanning electron microscope (SEM) image of the PVA-ANF / MXene@LM hydrogel prepared in Example 1 of the present invention.

[0029] Figure 2 This is a graph of the electromagnetic shielding effectiveness of the electromagnetic shielding hydrogels prepared in Examples 1-4 of the present invention at frequencies of 8.2 to 12.4 GHz.

[0030] Figure 3 This is the stress-strain curve of the PVA-ANF / MXene@LM hydrogel prepared in Example 1 of the present invention.

[0031] Figure 4 This is a graph of the resistance change rate of the PVA-ANF / MXene@LM hydrogel prepared in Example 1 of the present invention under different strains.

[0032] Figure 5 The sensing diagram of the PVA-ANF / MXene@LM hydrogel prepared in Example 1 of the present invention in response to the movement of different parts of the human body.

[0033] Figure 6 Schematic diagram of the PVA-ANF / MXene@LM hydrogel prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The present invention will be further described in detail below in conjunction with the accompanying drawings.

[0035] Example 1

[0036] Step 1: Etch Ti3AlC2 using hydrofluoric acid (HF) to obtain Ti3C2T x MXene; aramid fiber (PPTA) was dissolved in KOH and dimethyl sulfoxide (DMSO), centrifuged after stirring, and deionized water was added to obtain an aramid nanofiber dispersion; deionized water was added to 5g of polyvinyl alcohol and heated to prepare a PVA solution with a mass fraction of 10%.

[0037] Specifically, the Ti3C2T x The preparation process of MXene is as follows:

[0038] 1.0 g of LiF was weighed and dissolved in 20 ml of 9 mol / L hydrochloric acid solution, and then 1.0 g of Ti3AlC2MAX powder was added. After stirring at 35 ° C for one day, the mixture was centrifuged and washed several times until the pH was about 7. The supernatant was collected, ultrasonically treated for 1 h, and centrifuged at 3600 rpm for 1 h. The supernatant was taken to obtain the Ti3C2T x MXene.

[0039] Specifically, the preparation process of the aramid nanofiber is as follows:

[0040] 2.0 g of aramid fiber (PPTA) and 3.0 g of KOH were weighed and dissolved in 1 L of dimethyl sulfoxide. After stirring for one week, the mixture was centrifuged at 3000 rpm. The supernatant was taken and deionized water was added to obtain the aramid nanofiber dispersion.

[0041] Specifically, the PVA solution preparation process is as follows:

[0042] Weigh 5 g of polyvinyl alcohol and add deionized water to prepare a 50 g solution, stir and heat to 90° C., and the preparation is completed after the polyvinyl alcohol is dissolved.

[0043] The MXene dispersion and Ga were mixed in a mass ratio of 10:1 and ultrasonicated in an ultrasonic crusher to form a MXene@LM dispersion.

[0044] Step 2: After mixing the MXene@LM dispersion prepared in step 1 with the ANF dispersion in a mass ratio of 4:6, add 2 g of 10% PVA solution and stir until the solution is uniform.

[0045] Step 3: Pour the PVA-ANF / MXene@LM solution into the mold and place it in a refrigerator at -1°C.

[0046] Step 4: Thaw the PVA-ANF / MXene@LM solution in the mold of step 3 and separate the PVA-ANF / MXene@LM hydrogel from the mold.

[0047] Example 2

[0048] A method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel having electromagnetic shielding performance and strain sensing performance provided in step 1 of this embodiment 2

[0049] The preparation method of the MXene / aramid nanofiber electromagnetic shielding hydrogel is basically the same as that described in Example 1, except that:

[0050] The MXene dispersion and Ga were ultrasonically mixed at a mass ratio of 3:1; the rest of the operations were basically the same and will not be repeated here.

[0051] Step 2: After mixing the MXene@LM dispersion prepared in step 1 with the ANF dispersion in a mass ratio of 4:6, add 2 g of 10% PVA solution and stir until the solution is uniform.

[0052] Step 3: Pour the PVA-ANF / MXene@LM solution into the mold and place it in a refrigerator at -1°C.

[0053] Step 4: Thaw the PVA-ANF / MXene@LM solution in the mold of step 3 and separate the PVA-ANF / MXene@LM hydrogel from the mold.

[0054] Example 3

[0055] The method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel having electromagnetic shielding performance and strain sensing performance provided in step 1 of this embodiment 3 is basically the same as the method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel described in embodiment 1, except that:

[0056] The MXene dispersion and Ga were ultrasonically mixed at a mass ratio of 6:1; the rest of the operations were basically the same and will not be repeated here.

[0057] Step 2: After mixing the MXene@LM dispersion prepared in step 1 with the ANF dispersion in a mass ratio of 4:6, add 2 g of 10% PVA solution and stir until the solution is uniform.

[0058] Step 3: Pour the PVA-ANF / MXene@LM solution into the mold and place it in a refrigerator at -1°C.

[0059] Step 4: Thaw the PVA-ANF / MXene@LM solution in the mold of step 3 and separate the PVA-ANF / MXene@LM hydrogel from the mold.

[0060] Example 4

[0061] The method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel having electromagnetic shielding performance and strain sensing performance provided in step 1 of this embodiment 3 is basically the same as the method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel described in embodiment 1, except that:

[0062] The MXene dispersion and Ga were ultrasonically mixed at a mass ratio of 4:1; the rest of the operations were basically the same and will not be repeated here.

[0063] Step 2: After mixing the MXene dispersion prepared in step 1 with the ANF dispersion in a mass ratio of 4:6, add 2 g of 10% PVA solution and stir until the solution is uniform.

[0064] Step 3: Pour the PVA-ANF / MXene solution into the mold and refrigerate it in a refrigerator at 8°C.

[0065] Step 4: Thaw the PVA-ANF / MXene solution in the mold of step 3 and separate the PVA-ANF / MXene hydrogel from the mold.

[0066] Depend on Figure 1 It can be seen that the PVA-ANF / MXene@LM hydrogel prepared in Example 1 has a layered structure inside, which provides a structural basis for multiple reflections of electromagnetic waves inside. In addition, polyvinyl alcohol and aramid nanofibers are tightly combined with MXene@LM through hydrogen bonds, which is also the key to the excellent physical properties of electromagnetic shielding hydrogel.

[0067] In this type of layered structure, ANF and MXene@LM form a layered structure, and PVA forms a hydrogel together with the layered structure through internal network interlacing.

[0068] Figure 2 The electromagnetic shielding effectiveness diagram of the MXene / aramid nanofiber electromagnetic shielding hydrogel prepared in Examples 1-4 at 8.2-12.4 GHz is given. Figure 2 It can be concluded that the shielding effectiveness of Example 1 is about 35.7 dB, which is higher than the commercial electromagnetic shielding effectiveness of 20 dB.

[0069] Figure 3 The stress-strain curve of PVA-ANF / MXene@LM hydrogel is given, and its maximum stress reaches 210KPa, which is due to the unique network structure of PVA and the close combination of aramid nanofibers and MXene@LM.

[0070] Figure 4 The resistance change rate of PVA-ANF / MXene@LM hydrogel with strain is given. With different strain changes, PVA-ANF / MXene@LM hydrogel responds to electrical signals of different intensities, which can meet certain sensing requirements.

[0071] Figure 5 The electrical signals of PVA-ANF / MXene@LM hydrogel sensing the movement of different parts of the human body are given. The movement of different parts can be reflected by distinguishing the difference in electrical signals.

[0072] Figure 6 A schematic diagram of the PVA-ANF / MXene@LM hydrogel is given. It can be seen that the flexible and tough fibers are stacked with MXene@LM, and the MXene@LM is evenly distributed on the fiber mat.

Claims

1. A method for preparing MXene / aramid nanofiber electromagnetic shielding hydrogel, characterized in that: The steps include: Step 1: Ti3C2T x The MXene dispersion is ultrasonically mixed with the liquid metal to obtain a MXene@LM mixed solution; Step 2: adding the aramid nanofiber dispersion prepared by deprotonation and the PVA solution to the MXene@LM mixed solution, and stirring to obtain a uniform solution; Step 3: Pour the uniform solution into a mold and freeze it, then thaw and demold it to obtain PVA-ANF / MXene@LM hydrogel, i.e., MXene / aramid nanofiber electromagnetic shielding hydrogel.

2. The method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel according to claim 1, characterized in that: In step 1, Ti3C2T x The preparation process of MXene is as follows: Ti3AlC2 was etched with hydrofluoric acid (the molar ratio was 1:1) to obtain the Ti3C2T x MXene dispersion.

3. The method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel according to claim 1, characterized in that: In step 1, the ultrasonic mixing process of MXene and liquid metal is as follows: The MXene dispersion and liquid metal are mixed in a mass ratio of (3:1-10:1), and after ultrasonication in an ultrasonic crusher, a MXene@LM mixed solution is formed; The liquid metal is Ga.

4. The method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel according to claim 1, characterized in that: In step 2, the preparation process of the aramid nanofiber dispersion is as follows: KOH was dissolved in 1L of dimethyl sulfoxide, and then para-aramid fiber was added. After stirring, the mixture was centrifuged for 30 minutes at a centrifugal speed of 3000 rpm. Deionized water was added to obtain an aramid nanofiber dispersion, in which the mass ratio of KOH to para-aramid fiber was 3:

2.

5. The method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel according to claim 1, characterized in that: In step 2, the preparation process of the PVA solution is as follows: Deionized water was added to 5 g of polyvinyl alcohol and heated to prepare a PVA solution with a mass fraction of 10%.

6. The method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel according to claim 1, characterized in that: In the step 2, the MXene@LM mixed solution and the aramid nanofiber dispersion are mixed in a mass ratio of (2:8-8:2), and then 10% of the PVA solution is added and stirred (wherein the mixed dispersion and the PVA solution are mixed in a mass ratio of 1:1), and after the solution is uniform, a PVA-ANF / MXene@LM solution, i.e., a uniform solution, is obtained.

7. The method for preparing a MXene / aramid nanofiber electromagnetic shielding hydrogel according to claim 1, characterized in that: In the step 3, the uniform solution is poured into a mold and placed in a refrigerator at -1°C to 8°C, and then thawed and demolded to obtain the PVA-ANF / MXene@LM hydrogel.

8. A MXene / aramid nanofiber electromagnetic shielding hydrogel prepared by the method according to any one of claims 1 to 7, characterized in that: The hydrogel has a layered structure inside, which is a compact structure. PVA, ANF and MXene@LM are tightly connected by hydrogen bonds. This structure promotes the overlap of the conductive matrix. MXene is beneficial to the formation of a conductive path by covering the Ga surface. There are also dense fibers between the layers. The aramid fibers and MXene are tightly bound by hydrogen bonds. The hydrogel maintains high mechanical properties.

9. Application of the MXene / aramid nanofiber electromagnetic shielding hydrogel prepared by the method according to any one of claims 1 to 7, characterized in that: Applied to the field of electromagnetic shielding, which includes electromagnetic shielding and strain sensing.

10. The use of the MXene / aramid nanofiber electromagnetic shielding hydrogel according to claim 9, characterized in that: The electromagnetic shielding effectiveness can reach 35.7dB, and the thickness of the MXene / aramid nanofiber electromagnetic shielding hydrogel is 0.95-1.10mm.

Citation Information

Patent Citations

  • Aramid nanofiber / MXene composite conductive aerogel and preparation method thereof

    CN111040238A

  • Preparation method and application of aramid fiber reinforced PVA hydrogel

    CN115073774A

  • Preparation method and application of flexible multifunctional MXene / aramid nanofiber electromagnetic shielding film

    CN117887127A

  • Flexible ultrathin electromagnetic shielding and heat conducting difunctional composite film and preparation method thereof

    CN118085562A

  • Polyvinyl alcohol / liquid metal composite flexible hydrogel sensor as well as preparation method and application thereof

    CN118388796A

Cited By

  • Preparation method and application of bio-based composite nanofiber aerogel material with sandwich structure

    CN119978531A

  • Preparation method and application of MXene / liquid metal-based flexible composite film

    CN121687649A

  • Method for preparing mxene / liquid metal-based flexible composite film and application thereof

    CN121687649B